Peningkatan Hasil Belajar PAI tentang Taharah melalui Pembelajaran Berbasis Literasi Digital - Nugraha, Dera; Mansyur, Agus Salim; Zaqiah, Qiqi Yuliati (Universitas Muhammadiyah Magelang, 2020)
This research aims to find out the increase of students’ achievement in VII grade of Islamic Junior High School of Cendekia, Cianjur by using digital literacy-based learning. It was conducted in Taharah lesson. The subjects were 49 students of VII-a and VII-d including 22 males and 27 females. This Classroom Action Research was conducted within two cycles. Data collection techniques were done by test and observations. They were then analyzed using descriptive analysis techniques comparing the results among data of each cycles. The results indicated an increase of students’ achievement. In the first cycle it was only in low then raise into fair, and finally in good category. The score was going up from 57,2 to 71,9 and 83,6 at last.